(3aJhM eUQ hGdeZQHs - (3YHO GdQMef Hf YHO Gddg Hf YHO GdMce, CHh GdbGSe,J (B257 (3g` s ((3GdCScfOQjI s)
(3ChdgG (B:s
(3CNHQfG GdTjN CHhWGgQ CMeO Hf eMeO GdSdai GdCUHgGfi Yf YHO Gddg Hf YeQh Hf GdYGUi bGd (B: (3NdbJ GdOfjG Ydi NeS UhQ s
(3BNQgG (B:s
(3Yf SdjeGf Hf jSGQ (B: (3Cfge ZRhG EaQjbjI heYge HTQ cKjQ ef CUMGH QShd Gddg Udi Gddg Ydjg hSde ef GdegGLQjf hGdChdjf BNQg hGdMeO ddg QH GdYGdejf s
(3GdZQGai GdfGSN YGde cHjQ cGfJ dg cJGHI MSfI hcGf jQJRb HGdhQGbIs
(3HBNQ GdfSNI SeGYGJ efbhdI ef GdCUd GdefJSN efg HYVgG SfI (B570 (3hHYVgG SfI (B613s
(3QhGjI Ydi Hf GdMSf Hf Nda Hf bOjQ GdCROis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs